Bibliometric Analysis of Postgraduate Theses on Foot Diseases in Cattle in Turkey - İstek, Özmen (My University, 2025)
The aim of this study is to evaluate postgraduate theses on foot diseases observed in the cattle population in Türkiye within a holistic framework using the bibliographic analysis method, and to contribute to the academic studies that will follow. As the material and method used in the research, a search was made by typing the keyword “foot diseases” in the box where search term was made in the postgraduate theses section of the official website of the National Thesis Center of the Higher Education Institution. As a result of the search, it was determined that 16 of the n=25 theses, which were conducted between 1990 and 2024, were related to foot diseases in cattle, theses were related to foot diseases in sheep and goats, and one thesis, which was conducted in 1989, was related to medicine. In this research, the full text of 15 (93.75%) of the theses on the subject was reached, while one (6.25%) could not be reached. Twelve (75%) of the theses were found to be master's theses, and 4 (25%) were found to be doctoral theses. It was thought that very few of the postgraduate theses on the investigation of foot diseases in cattle were published as articles, and the studies conducted remained mainly at the master's level and did not contribute much to the doctoral overlap, and the impact of the literature as a publication should be increased.
Keywords: Bibliographic Analysis, Higher Education Institution, Postgraduate Thesis, Bovine Foot Diseases